VILLAHERMOSA-TABASCO WIND CHARACTERIZATION DURING 2008-2018 - Gomez Esteban, Gabriel; Andrade Velázquez, Mercedes (Kuxulkab', 2020)
This work focuses on the characterization of the winds that cross the city of Villahermosa, Tabasco, through the wind roses analysis from 2008 to 2018. The annual and quarterly graphs of the data obtained from the Comisión Nacional del Agua were analyzed. The results show that the dominant direction of the winds is from the East, which is associated with the low-level Jet present throughout the year. Secondary winds are associated with the different phenomena that predominate in the Gulf of Mexico, as is the case with the Alisios Winds and ‘Nortes’ in winter, while in summer, the components are associated with phenomena of ‘ Las Ondas del Este’. On the other hand, the study shows that El Niño-Southern Oscillation activity may influence the presence of other components.